1994
DOI: 10.1302/0301-620x.76b5.8083271
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of distal humeral fractures in the elderly

Abstract: We treated 49 patients at an average age of 80 years (75 to 90) with distal mostly intraarticular humeral fractures by open reduction. There were 8 class A, 13 class B and 28 class C fractures on Muller's classification. The patients were reviewed at a postoperative average of 18 months. The patients' assessment of the result was very good in 31%, good in 49%, fair in 15% and poor in 5 %. The flexion-extension range was very good in 41%, good in 44% and fair in 15%. The incidence of implant failure, pseudarthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
0
10

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(86 citation statements)
references
References 8 publications
5
71
0
10
Order By: Relevance
“…Our results do not imply that TER is necessarily the method of choice for such fractures, even in the older population. There are reports of good results after open reduction and internal fixation of these fractures in the elderly, [11][12][13][14][15] and if the surgeon feels that the fracture is amenable to stable fixation and early movement it is a good form of treatment. Most of these studies were in patients considerably younger than those in our series in which the only patient aged less than 81 years of age was a chronic alcoholic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results do not imply that TER is necessarily the method of choice for such fractures, even in the older population. There are reports of good results after open reduction and internal fixation of these fractures in the elderly, [11][12][13][14][15] and if the surgeon feels that the fracture is amenable to stable fixation and early movement it is a good form of treatment. Most of these studies were in patients considerably younger than those in our series in which the only patient aged less than 81 years of age was a chronic alcoholic.…”
Section: Discussionmentioning
confidence: 99%
“…This has also been noted by others, 31 and is in contrast to the reports of open reduction and internal fixation in which the emphasis is on early intensive physiotherapy. [1][2][3][11][12][13]15 While a mean follow-up of 17.8 months (12 to 34) may be considered to be a deficiency of our study, we feel that with the lessened demands placed upon the elbow and the increased mean age of our patient population, the good and excellent results should serve our patients well. Another limitation is that the study was not randomised, the selection of patients for TER being made on the limited possibility of securing stable fixation and starting early movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may occur in complex patterns which make operative treatment challenging and also prone to complications. Low fracture line, comminution and poor bone quality make the fixation more difficult [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The surgeon is faced with technical difficulties such as poor screw purchase and comminuted fracture fragments in soft fragile osteoporotic bone. Although some authors still advocate formal osteosynthesis with plates and report good to excellent results [4,11], Pajarinen and Bjorkenheim found that age over 50, poor bone quality, and immobilisation were poor prognostic factors for success of ORIF [10]. In a retrospective study of 45 patients over age 60, Korner et al found high postoperative rates, predominantly screw loosening and implant failure at the lateral column.…”
Section: Discussionmentioning
confidence: 99%